Soil Degassing From the Xianshuihe–Xiaojiang Fault System at the Eastern Boundary of the Chuan–Dian Rhombic Block, Southwest China - Sun, Yutao; Zhou, Xiaocheng; Yan, Yucong; Li, Jingchao; Fang, Wenya; Wang, Wanli; Liu, Yongmei (Frontiers in Earth Science, 2021)
The Chuan-Dian Region is situated in the middle part of the north-south seismic zone of the Chinese mainland, which is an area highly deformed in the eastern margin of the Tibetan Plateau. It is one of the principal areas monitoring for earthquake activities in China. In this study, the geochemical characteristics of the soil gas (CH4, H2, CO2, Rn and Hg) degassing as well as the relationship between gas degassing and fault activity were investigated in the Xianshuihe-Xiaojiang fault system (XXFS) at the eastern boundary of the Chuan-Dian rhombic block. The mean soil gas concentrations of CH4, H2, CO2, Rn and Hg in the XXFS were 8.1 ppm, 9.9 ppm, 0.5×104 ppm, 15.1 kBq/m3 and 12.9 ng/m3, respectively. The δ13CCO2 and δ13CCH4 values of the hot spring gases varied from -21.1‰ to -2.6‰ vs. PDB and -62.5‰ to 19‰ vs. PDB, respectively. The He-C isotopic ratios indicated the carbon in the northern and middle part of the XXFS might have the origin of deep fluids, whereas the carbon in southern part of the XXFS is of organic origin. The high concentrations of soil gas were distributed near the faults, indicating the fault could act as the channel of gas migration. The distributions of the high soil gas concentrations in the XXFS coincident with the highest stress and maximum strain rate, indicating the fault activity enhanced permeability so that emission rates of the gases were increased. The results of this study would be helpful not only to the gas degassing in the active fault zone but also to the earthquake monitoring.